Echocardiographic evaluation of verapamil in Friedreich's ataxia. Issue 4 (April 1986) - Casazza, F; Ferrari, F; Finocchiaro, G; Hartwig, J; Piccone, U; Tramarin, R; Morpurgo, M
Abstract : Nine patients with hypertrophic cardiomyopathy associated with Friedreich's ataxia were treated with the calcium antagonist verapamil, which is known to reduce myocardial hypertrophy and improve diastolic function in patients with idiopathic hypertrophic cardiomyopathy. Daily oral doses of 7 mg/kg were given for a mean (SD) of 24 (8) months. M mode echocardiography performed at the start of the study and at the end of follow up showed no significant difference between the treated group and an untreated control group of nine patients. Verapamil produced no changes in left ventricular wall thickness, mass index, left ventricular internal diameter, fractional shortening, peak normalised lengthening rate, peak rate of septal and posterior wall thinning, and time from minimum ventricular cavity dimension to mitral valve opening. Myocardial calcium overload has been suggested as a cause of cardiac disease in Friedreich's ataxia; however, verapamil had no beneficial effect on these patients with established myocardial hypertrophy.